Which interventions are effective at decreasing or increasing emergency department attendances or hospital admissions from long-term care facilities? A systematic review - Fiona Pearson; Barbara Hanratty; Gemma F Spiers; Robert O Barker; Daniel Stow; Ben Searle (BMJ Open)
Objective UK long-term care facility residents account for 185 000 emergency hospital admissions each year. Avoidance of unnecessary hospital transfers benefits residents, reduces demand on the healthcare systems but is difficult to implement. We synthesised evidence on interventions that influence unplanned hospital admissions or attendances by long-term care facility residents.Methods This is a systematic review of randomised controlled trials. PubMed, MEDLINE, EMBASE, ISI Web of Science, CINAHL and the Cochrane Library were searched from 2012 to 2022, building on a review published in 2013. We included randomised controlled trials that evaluated interventions that influence (decrease or increase) acute hospital admissions or attendances of long-term care facility residents. Risk of bias and evidence quality were assessed using Cochrane Risk Of Bias-2 and Grading of Recommendations Assessment, Development and Evaluation.Results Forty-three randomised studies were included in this review. A narrative synthesis was conducted and the weight of evidence described with vote counting. Advance care planning and goals of care setting appear to be effective at reducing hospitalisations from long-term care facilities. Other effective interventions, in order of increasing risk of bias, were: nurse practitioner/specialist input, palliative care intervention, influenza vaccination and enhancing access to intravenous therapies in long-term care facilities.Conclusions Factors that affect hospitalisation and emergency department attendances of long-term care facility residents are complex. This review supports the already established use of advance care planning and influenza vaccination to reduce unscheduled hospital attendances. It is likely that more than one intervention will be needed to impact on healthcare usage across the long-term care facility population. The findings of this review are useful to identify effective interventions that can be combined, as well as highlighting interventions that either need evaluation or are not effective at decreasing healthcare usage.PROSPERO registration number CRD42020169604.